Emergent presentation of Langerhans cell histiocytosis in a pediatric patient: Acute cerebellar involvement causing obstructive hydrocephalus requiring posterior fossa decompression - Rajderkar, Dhanashree A; Shah, Mrunal L; Shah, Jehan L (Indian Journal of Radiology and Imaging, 2017)
Langerhans cell histiocytosis (LCH) is a disorder of the monocyte-macrophage system that can be unifocal or systemic. Here, we present a pediatric case who initially presented with osseous LCH but again presented 6 years later emergently with cerebellar symptoms, cerebellar mass and obstructive hydrocephalus. Patient underwent biopsy of the cerebellum which was path proven intracranial LCH.
Keywords: Emergent decompression; intracranial Langerhans cell histiocytosis; obstructive hydrocephalus